Beyond the Fragile X protein: neighborhood characteristics explain individual differences in IQ and adaptive behaviors of Fragile X syndrome - McKinney, Walker S.; Corsmeier, Austin; Dapore, Ashley; Gross, Christina; Dominick, Kelli C.; Erickson, Craig A.; Schmitt, Lauren M. (Frontiers in Psychiatry, 2025)
BackgroundFragile X syndrome (FXS) is the most common inherited cause of intellectual disability and is caused by reduced or absent Fragile X messenger ribonucleoprotein (FMRP). Cognitive and adaptive skills widely vary among individuals with FXS, and these individual phenotypic differences are not fully accounted for by individual differences in FMRP expression. Social-environmental factors, including social determinants of health, may help further explain these individual differences, but these environmental factors have been under-studied in FXS.Methods175 participants with FXS (123 males; age range: 4–72 years) completed the Stanford-Binet, Fifth Edition to estimate IQ and a blood draw to quantify peripheral FMRP levels. Caregivers from a subset of participants also completed the Vineland Adaptive Behavior Scales. Neighborhood-level social-environmental information was extracted by linking participants’ home addresses to rankings of neighborhood resources (e.g., household income, pollution, healthcare access) from the Child Opportunity Index (COI). We calculated the unique variance in IQ and adaptive behaviors accounted for by these neighborhood-level social-environmental factors from the COI while covarying for FMRP expression.ResultsEven after accounting for individual differences in FMRP, numerous neighborhood factors were associated with greater IQ in males with FXS, including social resources and indicators of healthcare access. Different social-environment factors were associated with stronger adaptive skills in males with FXS, including economic and educational resources. Almost no neighborhood factors were associated with clinical outcomes in females.DiscussionOur finding of stronger links between neighborhood resources and clinical outcomes in males with FXS is consistent with previous work and may reflect increased reliance on social-environmental supports in males who typically have more significant intellectual and adaptive deficits than females. Consistent associations between greater social resources, higher IQ, and stronger adaptive skills suggest social support (e.g., social cohesion, resource and knowledge sharing) may be a particularly salient target for intervention. Associations between economic resources and adaptive communication skills also highlight the benefits of targeted economic supports for families affected by FXS. Together, our findings underscore the role of social determinants of health as key contributors to individual differences and the importance of considering these factors in clinical studies of FXS.